2019
DOI: 10.1038/s41598-019-49759-w
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide identification of and functional insights into the late embryogenesis abundant (LEA) gene family in bread wheat (Triticum aestivum)

Abstract: Late embryogenesis abundant (LEA) proteins are involved in the responses and adaptation of plants to various abiotic stresses, including dehydration, salinity, high temperature, and cold. Here, we report the first comprehensive survey of the LEA gene family in “Chinese Spring” wheat (Triticum aestivum). A total of 179 TaLEA genes were identified in T. aestivum and classified into eight groups. All TaLEA genes harbored the LEA conserved motif and had few introns. TaLEA genes belonging to the same group exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 49 publications
4
41
0
1
Order By: Relevance
“…Wheat seedlings were grown in a hydroponic culture for two weeks and root, stem and leaf tissues of the wheat seedlings were collected. For the abiotic stress treatment, seedlings were exposed to 20% PEG 6000 ( w / v ), high salinity (300 mM NaCl), high temperature (42 °C) and cold (4 °C) conditions as described previously [ 40 ]. In each treatment, the leaf tissues were collected every 12 h for 36 h. All samples were frozen in liquid nitrogen and stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Wheat seedlings were grown in a hydroponic culture for two weeks and root, stem and leaf tissues of the wheat seedlings were collected. For the abiotic stress treatment, seedlings were exposed to 20% PEG 6000 ( w / v ), high salinity (300 mM NaCl), high temperature (42 °C) and cold (4 °C) conditions as described previously [ 40 ]. In each treatment, the leaf tissues were collected every 12 h for 36 h. All samples were frozen in liquid nitrogen and stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Abiotic stresses, such as high temperature, high salinity/alkaline, extreme aridity, and cold or freezing, influence plant growth and often cause deficit in cellular water, thereby causing a series of changes, including biochemical alterations in gene expression, osmolytes, and the accumulation of specific proteins involved in the stress response. Late embryogenesis abundant proteins (LEAs) and abscisic acid-, stress-, and ripening-induced proteins (ASRs) are supposed to play crucial roles in the processes of drought resistance or other water-deficit stresses [ 1 , 2 , 3 , 4 , 5 ]. LEA genes have been characterized in plants ranging from algae to higher plants, as well as in invertebrates, fungi, and bacteria [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that “what determines the organ specificity of the autoimmune-inflammatory process may depend on food antigens resembling proteins of the organ being attacked. This applies to the brain and neuroinflammatory diseases, as to other organs and other diseases.” For example, the late-embryo-abundant group III protein family that is found in plants and seeds such as soybean, wheat, tomato, peanuts and in crustaceans as well, share the epitopes of 11 amino acid residues with α-synuclein (aSN) [ 25 , 26 , 27 , 28 , 29 , 30 ]. Furthermore, vertebrates, especially fish, fowl and mammals, are the main source of aSN, which after their consumption, can potentially pass the enteric barrier and reach the human brain.…”
Section: Introductionmentioning
confidence: 99%